The miserable mill - Snicket, Lemony; Helquist, Brett (New York, N.Y. : HarperCollins Publishers, 2000)
Accidents, evil plots, and general misfortune abound when, in their continuing search for a home, the Beaudelaire orphans are sent to live and work in a sinister lumber mill.
AAL
Trim Education
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Humorous stories